2018
DOI: 10.1186/s13287-018-0977-z
|View full text |Cite
|
Sign up to set email alerts
|

Current status and potential challenges of mesenchymal stem cell-based therapy for malignant gliomas

Abstract: Glioma, which accounts for more than 30% of primary central nervous system tumours, is characterised by symptoms such as headaches, epilepsy, and blurred vision. Glioblastoma multiforme is the most aggressive, malignant, and lethal brain tumour in adults. Even with progressive combination treatment with surgery, radiotherapy, and chemotherapy, the prognosis for glioma patients is still extremely poor. Compared with the poor outcome and slowly developing technologies for surgery and radiotherapy, the applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 92 publications
(85 reference statements)
1
64
0
Order By: Relevance
“…In MSCs group, low hypercellularity and mitosis index as well as mild invasive of tumor cells without pseudopalisading necrosis indicate that the anticancer effect of MSCs in a rat model of GBM. It has been shown that by means of tumour-specific tropism of MSCs can be transduced to deliver anticancer agents such as interleukins (IL-2, IL-7, IL-18, and IL-12), TRAIL, and interferon (IFN-β and IFN-γ) directly to glioma sites to kill tumour cells or to regulate immune responses [ 2 , 4 , 35 , 36 ]. Mild or limited invasive tumoral cells associated with low microvascular proliferation without pseudopalisading necrosis, in Ator + MSCs group shows that simultaneous utilization of MSCs and Ator can exert more anticancer activity against GBM rather than MSCs and Ator alone in experimental GBM model.…”
Section: Resultsmentioning
confidence: 99%
“…In MSCs group, low hypercellularity and mitosis index as well as mild invasive of tumor cells without pseudopalisading necrosis indicate that the anticancer effect of MSCs in a rat model of GBM. It has been shown that by means of tumour-specific tropism of MSCs can be transduced to deliver anticancer agents such as interleukins (IL-2, IL-7, IL-18, and IL-12), TRAIL, and interferon (IFN-β and IFN-γ) directly to glioma sites to kill tumour cells or to regulate immune responses [ 2 , 4 , 35 , 36 ]. Mild or limited invasive tumoral cells associated with low microvascular proliferation without pseudopalisading necrosis, in Ator + MSCs group shows that simultaneous utilization of MSCs and Ator can exert more anticancer activity against GBM rather than MSCs and Ator alone in experimental GBM model.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that use of MSCs as a carrier of IFNb may provide advantages over intratumoral gene therapy. In particular, the MSC approach is expected to be transient when applied in vivo, since cells may migrate out of the tumor, differentiate, or die (9,10). The adenovirus that they carry cannot replicate and is not integrated in the host genome, therefore this approach is incompatible with stable, long term exogenous gene expression (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, autologous MSCs may be isolated from the circulation, bone marrow, or adipose tissue, including lipoaspirates, cultivated in the laboratory, modified and expanded ex vivo, and then infused in the patient (4)(5)(6). The use of MSCs as a delivery vehicle for the therapeutic payload has been shown to home to and infiltrate the tumor site where they provide therapeutic transgene levels while shielding the gene transfer vector from immune recognition (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…GBM expresses a variety of proteins that bind to T cell surface receptors, leading to T cell dysfunction and apoptosis [ 1 , 2 ], and GBM microenvironment signals, such as TGF-β and IL-10, induce local and systemic immunosuppression [ 3 ]. Despite the introduction of concomitant and adjuvant radiotherapy and chemotherapy, patient prognosis remains unsatisfactory, with an almost 15 months median survival [ 4 6 ]. These poor outcomes are partially linked to extreme degrees of genetic and phenotypic variation, as well as therapeutic resistance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%